A simple computerised technique for estimating resting lip position and symmetry. Issue 2 (1st April 2021) - Mabvuure, Nigel Tapiwa; Klimach, Stefan; Hallam, Marc-James; Nduka, Charles
Abstract: The angle between the commisure–commisure and the endocantus–commisure lines (CCE angle) is approximately equal to the contralateral angle. A computerised technique for assessing the gross symmetry and position of the lips by comparing left- and right-sided CCE angles was developed. This study established (1) the repeatability of computerized CCE angle measurement; (2) mean CCE angle magnitudes in healthy controls and suggest a "normal" reference range. Two authors independently measured CCE angles on frontal repose facial photographs of 104 volunteers on three separate occasions using facial analysis software. Twenty right-sided hemifaces with the largest CCE differences were then mirrored in the sagittal plane to produce symmetrical photographs. Measurements were repeated by a single author. There was high agreement of angle measurements between authors (inter-rater ICC of 0.89) and within each authors' repeated measurements (intra-raters ICCs of 0.85 and 0.77). Differences in the mean right and left-sided CCE angles in controls were small but statistically significant (82.4° and 81.7°, respectively, mean absolute difference 2.2 ± 1.7°, p < 0.05). The mean absolute differences had a skewed distribution. The 2.5th and 97.5th centiles were therefore set as limits of the range of asymmetries which could be regarded as "normal" (95% reference range, or 95% reference interval): 0.2°–6.2°. Measurements of opposing CCE angles in symmetrical mirrored images were similar (82.4° versus 82.3°, mean absolute difference 0.6°, p > 0.05). In conclusion, computerised CCE angle measurement is highly repeatable and may be a useful tool with which to assess gross resting lip symmetry.